STUDY OF GEODESIC INSTRUMENTS PRODUCED IN LEADING EUROPEAN COUNTRIES IN OUR REPUBLIC - Kasimov Mahmud (Western European Studies, 2024)
This article explores the significance of advanced European-made geodetic instruments in Uzbekistan's surveying and cartography sector. The study compares key geodetic technologies, including GNSS receivers, robotic total stations, and 3D laser scanners, focusing on their accuracy, efficiency, and economic benefits. The results show that these tools significantly enhance measurement precision and reduce survey time by up to 30%, while lowering project costs by 20-25%. However, challenges such as a lack of local expertise and limited technical support infrastructure hinder the widespread adoption of these advanced technologies. The geodetic market in Uzbekistan is predicted to grow at a compound annual growth rate (CAGR) of 7.5% by 2030, with European instruments playing a critical role in major infrastructure projects and urban planning. Overall, the adoption of these technologies is expected to drive improved accuracy, cost-effectiveness, and efficiency in the country's land management and construction sectors.
Keywords: geodesy; European instruments; GNSS